2014
DOI: 10.1111/acer.12388
|View full text |Cite
|
Sign up to set email alerts
|

Stress Abolishes the Effect of Previous Chronic Ethanol Consumption on Drug Place Preference and on the Mesocorticolimbic Brain Pathway

Abstract: The present study indicates that previous EtOH consumption as well as stress exposure induces increased EtOH conditioning, which can be related to dopaminergic alterations in the PFC or NAc. Interestingly, concomitant exposure to both stimuli abolished each other's effect on conditioning and PFC or NAc alterations. This protective outcome can be related to the dopaminergic increase in the amygdala.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In an ethanol-induced CPP study 45 (dose: 2.0 g/kg), adult DBA/2 J mice spent around 60% of the test on the CS + , which is similar to our data in Swiss mice. DBA/2 J mice, however, exhibited a negative correlation between ethanol intake and ethanol-induced CPP 45 , whereas pre-exposure to ethanol potentiates ethanol conditioning in the Swiss mice 46 . Adolescent Swiss mice also show, when compared to adult counterparts, lower levels of sensitization to ethanol 6 yet after the sensitization ethanol intake escalates more pronounced in the adolescents than in the adults 47 , Studies with the outbred strain OF1 have shown that pre-exposure to ethanol or to stress during adolescence enhances subsequent cocaine-induced CPP 48 and ethanol self-administration 49 , respectively.…”
Section: Discussionmentioning
confidence: 83%
“…In an ethanol-induced CPP study 45 (dose: 2.0 g/kg), adult DBA/2 J mice spent around 60% of the test on the CS + , which is similar to our data in Swiss mice. DBA/2 J mice, however, exhibited a negative correlation between ethanol intake and ethanol-induced CPP 45 , whereas pre-exposure to ethanol potentiates ethanol conditioning in the Swiss mice 46 . Adolescent Swiss mice also show, when compared to adult counterparts, lower levels of sensitization to ethanol 6 yet after the sensitization ethanol intake escalates more pronounced in the adolescents than in the adults 47 , Studies with the outbred strain OF1 have shown that pre-exposure to ethanol or to stress during adolescence enhances subsequent cocaine-induced CPP 48 and ethanol self-administration 49 , respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Ethanol-withdrawal and stress change the activity of similar brain structures related to the encoding of motivational salience of a stimulus (i.e., mesocorticolimbic dopaminergic pathway) and emotional behavior (e.g., amygdala and other limbic structures) [4]. When experienced together, forcedswim stress and ethanol consumption increase dopaminergic content within the amygdala, abolishing drug conditioned place preference [47]. Stress induces the activation of dopamine release in medial prefrontal cortex neurons, which in turn inhibits dopamine release in the nucleus accumbens [48].…”
Section: Discussionmentioning
confidence: 99%
“…CPP was evaluated as described by Ref. [15] with small modifications. During the even days of conditioning phase (days 2, 4, 6 and 8), animals were s.c. treated with conessine (1.0 or 10.0 mg/kg) or vehicle one hour before i.p.…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…Control animals received vehicle and saline every day. Preconditioning and postconditioning tests were conducted as already described by [15]. Time spent (in seconds) in each compartment during preconditioning and postconditioning tests was measured by the behavioral analysis software ANY-maze (Stoelting Co., Wood Dale, IL-USA) and the compartment preference in postconditioning test was compared to the initial preference in preconditioning test (N = 9-10 animals per group).…”
Section: Conditioned Place Preferencementioning
confidence: 99%
See 1 more Smart Citation